Analysis of Sea Border Transportation in Indonesia, Case Study: Crossing Between Indonesia and Philippines (Bitung – Davao City) - Danny Faturachman; Aldyn Clinton Partahi Oloan; Fridolini (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2021)
Indonesia as an archipelagic country consists of thousands of islands and has a large sea area so that the required mode of transportation is sea transportation as a means of mobility and driving national economic development. In addition, Indonesian waters serve as a liaison between cities, as well as between countries. As a border on the island of Sulawesi, the city of Bitung is a link between Indonesia and the city of Davao City in the Philippines. For all of this, security for shipping, especially at the border, is needed to support the smooth delivery of goods by using Ferry Ro/Ro ships so that sea transportation activities in general and trade and economic activities between the two countries can run smoothly because maritime safety greatly affects the continuation of development efforts.